Frequency reconfigurable rectangular patch antenna for cognitive radio applications - Manjuanatha Kurugodu Hanumanthappa; Shilpa Mehta (International Journal of Electrical and Computer Engineering (IJECE), 2023)
A frequency reconfigurable microstrip transformed rectangular patch antenna consisting of two slots able to radiate in S-band and C-band is proposed. Spectrum occupancy is first analyzed using the data from literature and internet sources and hence spectrum holes are identified. A rectangular radiating patch is then designed for 5.8 GHz resonant frequency. A coaxial feed is used in the bottom by a suitable feed point. Two slots at an angle of +45 degree are made at the two corners. The electrical length of the patch is changed by using two varactor diodes in the slots. The varactors enable frequency reconfiguration in the band of frequencies that are unused or the spectral occupancy is very less. The return loss, voltage standing wave ratio (VSWR), and 2D-radiation patterns are analyzed for various values of the capacitances. high-frequency structure simulator (HFSS) is used for simulation. FR4 substrate which is economical, is used with height, h=1.6 mm, width W=25.33 mm, and length L=21.34 mm. On the substrate the rectangular patch is of width 15.73 mm and length 11.74 mm. The return loss and radiation patterns for different values of capacitances is presented. The tunability ratio obtained is 1.93. The results obtained agree with the standards.